Synthesis and antimicrobial activity of some new hydrazones of 4-fluorobenzoic acid hydrazide and 3-acetyl-2,5-disubstituted-1,3,4-oxadiazolines - (:unkn) unknown (ELSEVIER SCIENCE SA, 2002)
A series of hydrazide hydrazones and 1,3,4-oxadiazolines of 4-fluorobenzoic acid hydrazide were prepared and evaluated as potential antimicrobial agents and were tested for their antibacterial and antifungal activities against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans. From these compounds, 4-fluorobenzoic acid[(5-nitro-2-furanyl)methylene]hydrazide (1a) showed equal activity with ceftriaxone against S. aureus. In addition, the MIC values of compounds 1c, 1d and 2a for the same strain were in the range of those reported for ceftriaxone according to NCCLS 1997. (C) 2002 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: antimicrobial activity; hydrazones; 4-fluorobenzoic acid hydrazide; DERIVATIVES